Using Story Mapping Strategy and Reading Motivation to Improve Reading Narrative Comprehension Achievement of Tenth Graders of SMAN 1 Kotapadang - Firmansyah, Hendri; Istikomah, Istikomah; Hidayati, Sri (Linguists : Journal of Linguistics and Language Teaching, 2019)
The study was conducted to see whether or not there was a significant improvement in reading narrative comprehension achievement between the students who were taught by using Story Mapping and those who were taught by Guided Reading, to know what the students’ reading motivation, and to know whether or not reading motivation significantly contributed to reading narrative comprehension achievement of tenth grader of SMAN 1 Kotapadang Bengkulu. The experimental research with non-equivalent control design was applied in this study. The population was the tenth graders of SMAN 1 Kotapadang and sixty students were selected as the sample purposefully; they were equally grouped into experimental and control ones. To collect the data, Reading Comprehension Test and Motivation Reading Questionnaire (MRQ) were used. The results showed that there was significant improvement in reading narrative comprehension achievement of the students who were taught by Story Mapping, students’ reading motivation was high, and reading motivation was significantly contributed to reading narrative comprehension achievement of tenth graders of SMAN 1 Kotapadang.